Corpora: From theoretical linguistics to language teaching - Ikmi Nur Oktavianti (Universitas Ahmad Dahlan)
Corpus has gained its popularity in linguistics over the past five decades, from the computerized storage of English language in Survey of English Usage in 1959 to the ongoing development of Corpus of Contemporary American English. Because of the huge size of actual language data compiled in corpora, many linguists and language teachers working with English language have benefited from them in linguistic research and teaching practice. Up to now, there are innumerable English online corpora recording data from various genres, modes, and regions as well as corpus tools to analyze self-compiled corpus. The massive development of corpora, however, has not been widely discussed among English language researchers and practitioners in Indonesia, let alone in English language teaching. Although linguistics and language teaching are two inseparable and firmly related fields, corpus as a concept and product of linguistics seems ignored or even avoided. This paper then aims to review the nature of corpus and how it is used to assist linguistic analysis. More importantly, this paper discusses another possible application of corpus, e.g., the use of corpus in teaching language. Considering the nature and the benefits of using corpora, it is then important to promote the use of corpus to enhance English language teaching and learning, either directly in the classrooms or indirectly in materials development.